2010
DOI: 10.1155/2010/275804
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles for Octanoylated and Decanoylated Ghrelins in Regulating Appetite and Metabolism

Abstract: Since its identification in 1999, ghrelin has been identified in all vertebrate groups. The “active core” of ghrelin is highly conserved among vertebrates, suggesting its biological activity to be also conserved. In fish, both acylated forms of ghrelin have been identified; however, the ratio of the ghrelin-C8 to ghrelin-C10 is not as great as observed in mammals. In the tilapia (Oreochromis mossambicus), ghrelin-C10 is the major form of ghrelin. Since fish are known to inhabit every ecological niche on earth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…Thus, in other studies in fish in which GHRL treatment was through, i.p. injection changes in plasma glucose levels were noted (Schwandt et al 2010). Furthermore, the lack of changes in fatty acid levels is in agreement with that reported in mice under a comparable ICV treatment (Stark et al 2015).…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 90%
“…Thus, in other studies in fish in which GHRL treatment was through, i.p. injection changes in plasma glucose levels were noted (Schwandt et al 2010). Furthermore, the lack of changes in fatty acid levels is in agreement with that reported in mice under a comparable ICV treatment (Stark et al 2015).…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 90%
“…While cellular glucose levels were not measured in the present study, insulin would be expected to stimulate glucose uptake and cortisol and glucagon to stimulate glycogenolysis in hepatocytes, which should increase intracellular glucose levels [38,41]. Consistent with this hypothesis, glucose injection increased liver GHR1 mRNA level [52], and ghrelin injection caused hyperglycemia and increased liver GHR1 mRNA level in tilapia [14,56]. The rapid decrease in hepatocyte GHR1 but not GHR2 mRNA levels during culture is also consistent with regulation of GHR1 mRNA levels by cellular metabolic status (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The fact that the stimulatory effects of ghrelin on glucose transporters in both the intestine and liver are observed within the same time window suggests that this hormone is simultaneously promoting glucose absorption from the intestinal lumen to the circulation and glucose uptake from the blood to storage locations, thereby preventing a condition of hyperglycemia. The effects of ghrelin on glycemia seem, however, controversial within the literature, as previous studies have shown that administration of this hormone does not alter circulating glucose levels in rainbow trout34 while produces a significant increase in tilapia55. These species-specific discrepancies might be dependent on different dietary habits, although more studies would be needed to elucidate the species- and tissue-specific effects of ghrelin on metabolic partitioning, and glucose production in fishes.…”
Section: Discussionmentioning
confidence: 99%